A wavelet neural network approach to predict daily river discharge using meteorological data - Gursoy, Omer; Engin, Seref Naci (SAGE PUBLICATIONS LTD, 2019)
This paper reports some part of modelling and data analysis work carried out within the frame of a comprehensive project on the web-based development of watershed information system. This work basically aims to present the daily discharge predictions from the actual discharge along with the meteorological data using a wavelet neural network approach, which combines two methods: discrete wavelet transform and artificial neural networks. The wavelet-artificial neural network model developed provides a good fit with the measured data, in particular with zero discharge in the summer months and also with the peaks and sudden changes in discharge on the test data collected throughout the year. The results indicate that the wavelet-artificial neural network model based predictions are distinctly superior to that of conventional artificial neural network model that corresponds up to an 80% reduction in the mean-squared error between the artificial neural network model and measured data.
Keywords: Wavelet; artificial neural network; wavelet-artificial neural network; discharge; prediction; TRANSFORM; Automation & Control Systems; Instruments & Instrumentation